Efeito antioxidante e caracterização físico-química do flavonóide floranol - Francoise Vasconcelos Botelho (2007)
Increasing evidences support the oxidative modification of LDL as playing a potential role in atherosclerosis. In the present study, floranol (3,5,7,2-tetrahyroxy-6-methoxy-8-prenylflavanone), a flavonoid isolated from the roots of Dioclea grandiflora, successfully inhibited the oxidation of LDL in the presence of copper ions as measured by conjugated diene formation and thiobarbituric acid-reacting substances (TBARS). As the antioxidant mechanism may involve metal coordination, we have undertaken a detailed study of floranol interactions with Cu(II) and Fe(III) by combination of UVvisible (UVVis) and mass spectrometry and cyclic voltammetry measurements. The acidity constants of the ligand, as well as the stability constants of the metal complexes, were calculated. The pKa values of 6.58, 11.97 and 13.87 were determined and the following acidity order is proposed 7-OH > 5-OH > 2-OH. The best fit between experimental and calculated spectra was obtained assuming the formation of two Cu(II) complexes: [CuL] log = 19.34 ± 0.05 and [CuL2]2 log = 26.4 ± 0.10 and three Fe(III) complexes: [FeL3]3 log = 44.72 ± 0.09, [FeL2] log = 35.32 ± 0.08 and [FeL]+ log = 19.51 ± 0.04. In addition, copper and iron reduction is less favorable in the presence of floranol. These results indicate that floranol can efficiently bind Cu(II) and Fe(III) ions thus preventing their effect on LDL oxidation. Another antioxidant mechanism of flavonoids is its ability to scavenge free radicals. We evaluated the antioxidant effect of floranol on activated murine macrophages in apolipoprotein E (ApoE-/-) and inducible nitric synthase (iNOS-/-) knockout mice comparing to the wild-type strain C57Bl/6 by chemiluminescence. It was demonstrated the attenuating effect of different concentrations of floranol on zymosan elicited murine macrophage oxidative burst from three experimental strains of mice. Altogether the data obtained in this study showed that floranol act as an antioxidant on capacity to chelate iron and copper ions and through a direct interaction with free radicals.